Increased Amplitude of Low-Frequency Fluctuation in Right Angular Gyrus and Left Superior Occipital Gyrus Negatively Correlated With Heroin Use - Luo, Jing; Yang, Ru; Yang, Wenhan; Duan, Chunmei; Deng, Yuan; Zhang, Jun; Chen, Jiyuan; Liu, Jun (Frontiers in Psychiatry, 2020)
Abnormal amplitude of low-frequency fluctuation has been implicated in heroin addiction. However, previous studies lacked consistency and didn’t consider the impact of confounding factors such as methadone and alcohol. Fifty-one heroin-dependent (HD) individuals and 40 healthy controls underwent resting-state functional magnetic resonance imaging. The ‘amplitude of low-frequency fluctuation’ (ALFF) value was calculated and support vector machine (SVM) classification analysis was applied to analyze the data. Compared with healthy controls, heroin addicts exhibited increased ALFF in the right angular gyrus (AG) and left superior occipital gyrus (SOG). A negative correlation was observed between increased ALFF in the right angular gyrus and left superior occipital gyrus and the duration of heroin use (p1=0.004, r1=-0.426; p2=0.009, r2=-0.361). Moreover, the ALFF in the right AG and left SOG could discriminate the HD subjects from the controls with acceptable accuracy (Acc1=64.85%, p1=0.004; Acc2=63.80%, p2=0.005). HD patients showed abnormal ALFF in the brain areas of semantic memory and visual network. The longer HD individuals abused heroin, the less the ALFF of associated brain regions increased. These observed pattern suggested that accumulative effect heroin’ neurotoxicity overpowered self-recovery of the brain and may be applied as a potential biomarker to identify HD individuals from the controls.